Sistem Informasi Wisata Kuliner di Kabupaten Lebak Berbasis Web - Ahmad Surahmat; Tubagus Dedy Fuady (Teknik Informatika Fakultas Ilmu Komputer, 2022)
Technological developments are increasingly rapid and easy to use, one of which is the development of information technology which can also contribute to the existence of an area that has culinary tourism potential. In the business world, the role of technology is very important, and it can be said that it has become a primary need for entrepreneurs at this time. Likewise for culinary, which has utilized the internet network to present various information, both from information on places, menus, and prices in the field of information technology. However, for culinary information in Lebak Regency on a website, while this is still incomplete and there is no website that specializes in culinary tourism in Lebak Regency. Therefore, a web-based culinary tourism information system application design is needed in Lebak Regency to make it easier for the public to find culinary information in Lebak Regency. System design and implementation will begin with system requirements analysis or known as system requirements analysis. This is intended to obtain the appropriate system specifications. In the design stage. Unified modeling language (UML) is used to clearly describe business processes. The test results of the website-based culinary tourism information system in Lebak Regency show that the features contained in the application can work well such as managing culinary data, managing admin data, managing member data. This information system has three users on the system, namely admin, member and user.